Trust us : reproducing the nation and the Scandinavian nationalist populist parties - Hellström, Anders (Berghahn Books, 2016)
In Scandinavia, there is separation in the electorate between those who embrace diversity and those who wish for tighter bonds between people and nation. This book focuses on three nationalist populist parties in Scandinavia - the Sweden Democrats, the Progress Party in Norway, and the Danish People's Party. In order to affect domestic politics by addressing this conflict of diversity versus homogeneity, these parties must enter the national parliament while earning the nation's trust. Of the three, the Sweden Democrats have yet to earn the trust of the mainstream, leading to polarized and emotionally driven public debate that raises the question of national identity and what is understood as the common man.